Author Correction: A reassortant H9N2 influenza virus containing 2009 pandemic H1N1 internal-protein genes acquired enhanced pig-to-pig transmission after serial passages in swine. Issue 1 (December 2018) - Mancera Gracia, José; Van den Hoecke, Silvie; Richt, Juergen; Ma, Wenjun; Saelens, Xavier; Van Reeth, Kristien
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.